Lesion of the dorsal hippocampus alters the time–course evolution of corticosterone rise in the ventral hippocampus after stress. Issue 10 (3rd July 2019) - Piérard, Christophe; Dorey, Rodolphe; Corio, Marc; Béracochéa, Daniel
Abstract : We previously showed that an acute stress-induced an early corticosterone rise in the dorsal hippocampus (dHPC) and a delayed one in the ventral hippocampus (vHPC). Congruently, we hypothesized that the dHPC may influence the time–course evolution of poststress glucocorticoid rise in the vHPC. To probe this issue, we performed ibotenic acid lesions of the dHPC and measured by microdialysis the time–course evolution of corticosterone rise in the vHPC after an acute stress delivery. In nonstress condition, we showed that the dHPC lesion induced a significant increase of corticosterone both in plasma and in the vHPC. In addition, an acute stress (electric footshocks) induced a faster and more sustained corticosterone rise in the vHPC of dHPC-lesioned animals, as compared to sham-operated ones. This study provides new found evidence to the effect that the dHPC lesion alters the time–course evolution of corticosterone rise within the vHPC after stress.